Breakdown of classical paradigms in relation to membrane structure and functions - Frias, Maria de Los Angeles (2021)
Updates of the mosaic fluid membrane model implicitly sustain the paradigms that bilayers are closed systems conserving a state of fluidity and behaving as a dielectric slab. All of them are a consequence of disregarding water as part of the membrane structure and its essential role in the thermodynamics and kinetics of membrane response to bioeffectors. A correlation of the thermodynamic properties with the structural features of water makes possible to introduce the lipid membrane as a responsive structure due to the relaxation of water rearrangements in the kinetics of bioeffectors' interactions. This analysis concludes that the lipid membranes are open systems and, according to thermodynamic of irreversible formalism, bilayers and monolayers can be reasonable compared under controlled conditions. The inclusion of water in the complex structure makes feasible to reconsider the concept of dielectric slab and fluidity.